The effect of past use of oral contraceptive on bone mineral density, bone biochemical markers and muscle strength in healthy pre and post menopausal women - Abourazzak Fatima; El Mansouri Laila; Allali Fadoua; Ichchou Linda; Khazzani Hamza; Bennani Loubna; Abouqal Redouane; Hajjaj-Hassouni Najia (BMC, 2009)
Abstract Background during adulthood, most studies have reported that oral contraceptive (OC) pills had neutral, or possibly beneficial effect on bone health. We proposed this study of pre and post menopausal women assessing BMD, bone biochemical markers and physical performance among OC past users and comparable women who have never use Ocs. Methods A cross-sectional study comparing the bone density, bone biochemical markers (osteocalcin, CTX) and three measures to assess physical performance: timed get-up-and-go test "TGUG", five-times-sit-to-stand test "5 TSTS" and 8-feet speed walk "8 FSW" of users and never users OC. We were recruited 210 women who used OC for at least 2 years with that of 200 nonusers was carried out in pre and postmenopausal women (24-86 years). Results when analysing the whole population, BMD and biochemical markers values were similar for Ocs past users and control subjects. However when analysing the subgroup of premenopausal women, there was a statistically significant difference between users and never-users in osteocalcin (15,5 ± 7 ng/ml vs 21,6 ± 9 ng/ml; p = 0,003) and CTX (0,30 ± 0,1 ng/ml vs 0,41 ± 0,2 ng/ml; p = 0,025). This difference persisted after adjustment for age, BMI, age at menarche and number of pregnancies. In contrast, in post menopausal women, there was no difference in bone biochemical markers between OC users and the control. On the other hand OC past users had a significant greater performance than did the never users group. And when analysing the physical performance tests by quartile OC duration we found a significant negative association between the three tests and the use of OC more than 10 years. Conclusion the funding show no evidence of a significant difference in BMD between Ocs users and never user control groups, a decrease in bone turn over in OC pre menopausal users and a greater physical performances in patients who used OC up than 10 years.